2003
DOI: 10.1111/j.1747-4469.2003.tb00209.x
|View full text |Cite
|
Sign up to set email alerts
|

In Their Own Words: How Ordinary People Construct the Legal World

Abstract: A wave of scholarship about legal consciousness has demonstrated how law shapes the everyday lives of ordinary people (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 15 publications
2
55
0
Order By: Relevance
“…She also understood the potential that legal advocacy has in defending her right to decent, affordable housing. This was a common feeling among low-income householders in this study, though many also suggested that trying to find legal representation would involve confronting an inefficient bureaucratic process compounded by a lack of free or low-cost legal services (Ewick and Silbey, 1998; Marshall and Barclay, 2003). This begs the question: in what ways are the housing problems of the poor remedied through legal services offered within the context of their healthcare facilities?…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…She also understood the potential that legal advocacy has in defending her right to decent, affordable housing. This was a common feeling among low-income householders in this study, though many also suggested that trying to find legal representation would involve confronting an inefficient bureaucratic process compounded by a lack of free or low-cost legal services (Ewick and Silbey, 1998; Marshall and Barclay, 2003). This begs the question: in what ways are the housing problems of the poor remedied through legal services offered within the context of their healthcare facilities?…”
Section: Resultsmentioning
confidence: 91%
“…Consistent with the objectives of health care reform, programs such as MLP have the potential to not just serve as “band-aids” for medical and legal problems, but to address inadequate enforcement of current laws especially those related to housing. This is especially promising for vulnerable groups who have limited access to legal services since in addition to financial barriers lawyers and other bureaucrats are often perceived with scrutiny and distrust, a perspective that is exemplified in the quote by a non-MLP participant (Eileen on page 7) and otherwise well-established in the literature (Ewick and Silbey, 1998; Marshall and Barclay, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…Do those who perceive a wrong simply tell the wrong-doer, do they tell others, or do they ignore it? Following Ewick and Silbey’s (1998) groundbreaking work on the common place of law, a growing body of literature has taken up these and related questions of legal consciousness and mobilization (e.g., Albiston 2005; Connolly 2002; Fleury-Steiner 2003; Hoffman 2005; Litowitz 2000; Lovell 2006; Marshall 2005; Marshall and Barclay 2003; Richman 2001). Central to these studies are the interrelated processes by which individuals first come to experience or perceive some wrong and then do something about it.…”
mentioning
confidence: 99%
“…The caseworkers and volunteers who helped people with their cases learned a legal game (Lens ; Marshall and Barclay ; Ewick and Silbey ) that was not entirely humanitarian: assisting people classified as victims. The event was something that happened to people, not something that defined who they were.…”
Section: Resultsmentioning
confidence: 99%